Oral breathing and speech disorders in children - Silvia F. Hitos; Renata Arakaki; Dirceu Solé; Luc L.M. Weckx (Elsevier, 2013)
Objective: To assess speech alterations in mouth-breathing children, and to correlate them with the respiratory type, etiology, gender, and age. Method: A total of 439 mouth-breathers were evaluated, aged between 4 and 12 years. The presence of speech alterations in children older than 5 years was considered delayed speech development. The observed alterations were tongue interposition (TI), frontal lisp (FL), articulatory disorders (AD), sound omissions (SO), and lateral lisp (LL). The etiology of mouth breathing, gender, age, respiratory type, and speech disorders were correlated. Results: Speech alterations were diagnosed in 31.2% of patients, unrelated to the respiratory type: oral or mixed. Increased frequency of articulatory disorders and more than one speech disorder were observed in males. TI was observed in 53.3% patients, followed by AD in 26.3%, and by FL in 21.9%. The co-occurrence of two or more speech alterations was observed in 24.8% of the children. Conclusion: Mouth breathing can affect speech development, socialization, and school performance. Early detection of mouth breathing is essential to prevent and minimize its negative effects on the overall development of individuals. Resumo: Objetivo: Verificar alterações na fala em crianças respiradoras orais e relacioná-las com o tipo respiratório, a etiologia, o gênero e a idade. Método: Foram avaliados 439 respiradores orais com idade entre quatro e 12 anos. Considerou-se atraso no desenvolvimento de fala a presença de alterações em crianças acima de cinco anos de idade. As alterações observadas foram interposição de língua (IL), ceceio frontal (CF), troca articulatória (TA), omissões (OM) e ceceio lateral (CL). Relacionou-se etiologia da respiração oral, gênero, idade, tipo respiratório e alterações de fala. Resultados: Alterações de fala foram diagnosticadas em 31,2% dos pacientes sem relação com o tipo respiratório: oral ou misto. Maior frequência de trocas articulatórias e mais de uma alteração de fala ocorreram no gênero masculino. IL foi documentada em 53,3% pacientes, seguida por TA em 26,3% e CF em 21,9%. Concomitância de duas ou mais alterações de fala ocorreu em 24,8% das crianças. Conclusão: Respirar pela boca pode afetar o desenvolvimento da fala, a socialização e o desempenho escolar. A detecção precoce da respiração oral é essencial para prevenir e minimizar seus efeitos negativos sobre o desenvolvimento global dos indivíduos. Keywords: Joint disorders, Mouth breathing, Rhinitis, Palatine tonsils, Adenoid, Palavras-chave: Transtornos da articulação, Respiração bucal, Rinite, Amígdala, Adenoide